2018
DOI: 10.6007/ijarbss/v7-i14/3689
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Academic Achievement in Online Peer Learning among Undergraduate Students in a Malaysian Public University

Abstract: An online peer learning through social media tools such as Facebook, Twitter, YouTube and Instagram has been networking interrelated undergraduates as social groups in higher learning institutions. In that respect, it has become an emerging phenomenon in the academia. Yet, not much is known about the effect of social media on the undergraduates" academic achievement. Therefore, the main purpose of this study is to identify the relationship of students' peer engagement, academic self-efficacy, social influence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…Based on the study results, it was found that the quality of peer relationships plays a significant role in students' academic motivation. Even in an online context, this finding seemed to be in line with previous studies (Amin et al, 2018;Buote et al, 2007;Willard W Hartup & Stevens, 1997;Hosan & Hoglund, 2017;Razak & See, 2010;Wentzel & Watkins, 2002) good academic achievement. In this case, peers can be referred to as academic enablers who can facilitate student participation in class (Wentzel & Watkins, 2002).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Based on the study results, it was found that the quality of peer relationships plays a significant role in students' academic motivation. Even in an online context, this finding seemed to be in line with previous studies (Amin et al, 2018;Buote et al, 2007;Willard W Hartup & Stevens, 1997;Hosan & Hoglund, 2017;Razak & See, 2010;Wentzel & Watkins, 2002) good academic achievement. In this case, peers can be referred to as academic enablers who can facilitate student participation in class (Wentzel & Watkins, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Another prominent factor is peer relationships. Through peer relationships, students can get rewards, reinforcement, or pressure (Elliot, Dweck, & Yeager, 2017), such as feedback, formation of achievement parameters, and collaboration (Amin, Hassan, & Jalil, 2018).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Malaysian researchers have recently broadened their study on psychological impact of academic performance, some psychological factors which have found to have significant connection with academic performance in tertiary level includes emotional intelligence, achievement motivation, self-efficacy and self-regulated learning strategies (Mahyuddin, Elias & Noordin, 2009;Elias, Mustafa, Roslan & Noah, 2011;Yusuf, 2011;Amin, Hassan & Jalil, 2018). To understand the impact better, this present study focuses on exploring the significance of three psychological factors (self-efficacy, motivation and learning strategy) and also added the impact of demographic factor which is age in determining the academic performance of Malaysian undergraduate students.…”
Section: Introductionmentioning
confidence: 99%